PENGARUH PERSONAL HYGIENE DAN KONDISI FISIK RUMAH SERTA PENGGUNAAN AIR SUNGAI TERHADAP KEJADIAN DERMATITIS KONTAK IRITAN DAN INFEKSI PADA MASYARAKAT DI KECAMATAN BATUNADUA KOTA PADANGSIDIMPUAN TAHUN 2015 - Harahap, Alprida . (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Dermatitis is a skin disease which is often found in the people of Batunadua Subdistrict. It ranked thesecond of ten leading diseases at Batunadua Primary Health Care (PHC) in 2014 with the prevalence of3.26%. Some factors which can influence the incidence of this disease are chemical substance,microorganism, and environment. Detergent as a chemical substance is one of the cause of irritantcontact dermatitis. Bad personal hygiene and home physical condition can easily be transmitted by skindiseases such as dermatitis infection which is caused by microorganism.The objective of the research was to analyze the influence of personal hygiene, home physicalcondition, and river water on the incidence of irritant contact dermatitis and infection. The research wasan analytic survey with case control design. The samples were 60 respondents, with 60 case group and 60control group.The study found of the analysis with chi square showed that there was the influence of bodycleanliness, towel cleanliness, beds, floors, walls, overcrowded, lighting, humidity, the frequency of theuse of river water, and the use of river water for bath, wash and lavatory on the incidence of irritantcontact dermatitis and infection. The result of the statistic test with multiple regresi logistic showed thatsome factors which influenced the incidence of irritant contact dermatitis and infection were bodycleanliness, towel cleanliness, beds, floors, lighting, the use of river water, and the frequency of the use ofriver water at the highest OR was beds cleanliness with OR=3.645 (95%CI 2.156-21.131).It is suggested to Dinas Kesehatan Padangsidimpuan and Batunadua Primary Health Center(PHC) make promotion and preventive efforts by providing information facilities such as leaflets andbanners about the risk factors for being affected by irritant contact dermatitis and infection which iseasily accessed by the people.